Xylitol Hydrogenolysis over Ruthenium‐Based Catalysts: Effect of Alkaline Promoters and Basic Oxide‐Modified Catalysts. Issue 12 (2nd May 2017) - Rivière, Maxime; Perret, Noémie; Cabiac, Amandine; Delcroix, Damien; Pinel, Catherine; Besson, Michèle
Abstract: The aqueous‐phase hydrogenolysis of xylitol into glycols over Ru/C was performed in the presence and absence of a wide range of concentrations of Ca(OH)2 to investigate the reaction pathway. Without base, epimerization and cascade decarbonylation were the predominant reactions with high selectivities to C5 and C4 alditols and light alkanes at full conversion. Glycol production was obtained by the addition of Ca(OH)2 to promote the retro‐aldol reaction. It competed with reactions without base and became the main reaction for a OH − / xylitol molar ratio R mol (OH/xylitol) of 0.13, and high selectivities to glycols (56 %) and glycerol (16 %) were observed. However, lactate was a byproduct at up to 27 % with a high base amount ( R mol (OH/xylitol)=0.68). Bifunctional Ru/metal oxide/C catalysts (metal: Zn, Sn, Mn, Sr, W) were synthesized and were able to cleave the C−C bond into glycols without a base promoter. The 3.1 wt %Ru/MnO(4.5 %)/C catalyst was the most active (220 h −1 ) with reasonable selectivity to glycols (22 %) and glycerol (10 %) and a low production of lactate (<1 %). Nevertheless, metal oxide leaching of the catalyst was observed likely because of the production of traces of lactate. Abstract : Let's split : The aqueous‐phase hydrogenolysis of xylitol into glycols over Ru/C is performed in the presence and absence of a wide range of concentrations of Ca(OH)2 to investigate the reaction pathway. Without base, epimerization and cascade decarbonylation are the predominant reactions with high selectivities to C5 and C4 alditols and light alkanes at full conversion. Glycol production is obtained by the addition of Ca(OH)2 to promote the retro‐aldol reaction.